2020
DOI: 10.1097/md.0000000000021040
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tai Chi Yunshou on upper limb function and balance in stroke survivors

Abstract: Background: Functional disability is the most common disorder that occurs after stroke and seriously affects the quality of life of stroke survivors. Tai Chi Yunshou (TCY), a fundamental form of Tai Chi, is a simple, convenient, and economical exercise therapy from ancient China. Some clinical trials have reported that it improves upper limb function and balance during stroke rehabilitation. Thus, we plan to conduct a systematic review to investigate the effects of TCY in stroke survivors. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Among these 59 studies, the data from only 38 could be extracted for TSA. Studies were excluded from the TSA if they: (1) were conference abstracts [ 29 , 30 , 31 ]; (2) performed only single-group before–after comparison [ 32 ]; (3) lacked raw data, which could not be obtained from the cited articles [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]; or (4) did not report the necessary outcome measures (gait speed or balance) [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Among these 59 studies, the data from only 38 could be extracted for TSA. Studies were excluded from the TSA if they: (1) were conference abstracts [ 29 , 30 , 31 ]; (2) performed only single-group before–after comparison [ 32 ]; (3) lacked raw data, which could not be obtained from the cited articles [ 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 ]; or (4) did not report the necessary outcome measures (gait speed or balance) [ 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 ].…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have demonstrated the “Loud Hand” of Tai Chi significantly improved the limb motor function, with strengthening the internal and external rotation of the shoulder, promoting forward flexion and abduction of the shoulder and alleviating shoulder pain ( Lyu et al, 2018 ; Luo et al, 2020 ; You et al, 2021 ). WAT applies round rotation motion for both trunk and limb training.…”
Section: Discussionmentioning
confidence: 99%
“…At present, studies on the intervention effect of Tai Chi Yunshou on the balance and motor function of stroke patients are all randomized controlled trials or study protocols and lack exhaustive evidence-based medicine support (19). Therefore, it is necessary to perform a systematic review and meta-analysis of the existing evidence.…”
Section: Introductionmentioning
confidence: 99%